Levels of BPA in makdous, a traditional Syrian food, using solid-phase extraction followed by HPLC (Brazilian Journal of Pharmaceutical Sciences, 2022)
Bisphenol A (BPA), an endocrine disrupter, can migrate from packaging material into food stuff. This research was designed to measure BPA levels in makdous, a traditional Syrian food. Forty three samples of makdous stored in different plastic containers (polyethylene (PE), polypropylene (PP), and unspecified plastic containers) were analyzed every 3 months for one year beginning July 2017. Quantification of BPA was carried out by an RP-HPLC system equipped with fluorescence detector after solid phase extraction. Migration was found in PE and PP plastic containers with slight differences. Statistically significant differences in BPA levels were observed between samples assayed after two weeks of preparation and samples assayed after 12 months (mean 16.32 vs. 38.26 μg/kg, p value=0.003). According to these amounts, BPA levels were all under the specific migration limit of 0.05 mg/kg as newly referred in Regulation (EU) No 2018/213. These levels of exposure would only contribute to 2.15% and 2.75% of the EFSA t-TDI in both men and women respectively based on mean dietary exposure estimates derived from a 24-h dietary information study from 875 participants. Hence there are no concerns about potential health risks from makdous consumption.